Expression and hepatobiliary transport characteristics of the concentrative and equilibrative nucleoside transporters in sandwich-cultured human hepatocytes - Govindarajan, Rajgopal (American Physiological Society, 2008)
We previously reported that both the concentrative (hCNT) and equilibrative (hENT) nucleoside transporters are expressed in the human liver (21). Here we report a study that investigated the expression of these transporters (transcripts and proteins) and their role in the hepatobiliary transport of nucleosides/nucleoside drugs using sandwich-cultured human hepatocytes. In the hepatic tissue, the rank order of the mRNA expression of the transporters was hCNT1 ≈ hENT1 > hENT2 ≈ hCNT2 > hCNT3. In sandwich-cultured hepatocytes, the mRNA expression of hCNT2 and hENT2 was comparable to that in hepatic tissue, whereas the expression of corresponding transporters in the two-dimensional hepatocyte cultures was lower. Colocalization studies demonstrated predominant localization of these transporters at the sinusoidal membrane and of hENT1, hCNT1, and hCNT2 at the canalicular membrane. In the sandwich-cultured hepatocytes, ENTs were the major contributors to the transport of thymidine (hENT1, 63%; hENT2, 23%) or guanosine (hENT1, 53%; hENT2, 24%) into the hepatocytes followed by hCNT1 (10%) for thymidine or hCNT2 (23%) for guanosine. Although ribavirin was predominately transported (89%) into the hepatocytes by hENT1, fialuridine (FIAU) was transported by both hENT1 (30%) and hCNTs (61%). The extensively metabolized natural nucleosides were not effluxed into the bile, whereas significant biliary-efflux was observed of FIAU (19%), ribavirin (30%), and formycin B (35%). We conclude that the hepatic activity of hENT1 and hCNT1/2 transporters will determine the in vivo hepatic distribution and therefore the efficacy and/or toxicity of nucleoside drugs used to treat hepatic diseases.